Investigation of relationship between smoking behavior and psychological variables according to different stages of change - Bardak, Furkan; Demir, İrem; Dinar, Cansel; Doğan, Dilan; Alparslan, Merve; Yalçınkaya Alkar, Özden (Journal of Dependence, 2016)
Objective: The aim of this study is to examine whether smoking behavior and related psychological variables differ according to the stages of change (precontemplation, contemplation, preparation, action and maintenance) of the smokers.Method: The total of 504 voluntary individuals, who is still smokers or people who had been smokers but were given up within the last year, were participated in the study. Of the total, sample consisted of 197 women (38.9%), and 307 men (60.6%). Data were obtained with Fagerstrom Tolerance Questionnaire, Decisional Balance Scale, Self-Efficacy Questionnaire, The Multidimentional Scale of Perceived Social Support, Perceived Stress Scale. Data were analyzed using the independent sample t-test and one-way analysis of variance (ANOVA).Results: The results of the analysis indicated that there is a significant difference between individuals’ attempts to quit smoking and the stages of change; also people who are in preparation stage had far more attempt to quitting smoking with regard to pre-contemplation and contemplation stages.Conclusion: There are significant differences between the perceived pros and cons of smoking according to different stages of change as well; and pros of smoking increased from pre-contemplation to contemplation and preparation. There are statistically significant differences between smokers who were in different stages of change in terms of self-efficacy for quitting smoking and additionally people who were in action and preparation were found to have higher levels of self-efficacy than those in the precontemplation and contemplation stages. Ultimately this study’s strengths, limitations and implications were discussed in the framework of relevant literature.
Keywords: Smoking behavior; stages of change; pros and cons of smoking; selfefficacy